The role of communications in the resilience of risk group in Kuching, Sarawak, during the dispersal of COVID-19 virus - Kamaruzzaman Abdul Manan; Norazreen Sapiee; Nurhafza Mohamad Mustafa; Wan Norshira Wan Mohd Ghazali (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Covid-19 Pandemic has significantly interfered with all aspects of human life. Notably, this dangerous epidemic has a more significant impact on the risk group. It has caused them to feel stress, fear, and suffering from the ripple effect of Covid-19. Hence, this disruption occurred instantaneously, requiring people to demonstrate noteworthy adaptability and resiliency through communication. Therefore, this study examined the two dimensions of communication, namely self-centred communication (knowledge and optimistic thinking) and external communication (family support and media exposure), in predicting the resilience among the risk group in Kuching, Sarawak. The data collection was during the movement control order, so the distribution of the online questionnaire used voluntary response sampling to the target respondents through WhatsApp and social media accounts. Data collected was analysed using Partial Least Squares analyses. The results show that knowledge, optimistic thinking, and family support significantly correlate with the resilience of the risk group. Moreover, the self-centred communication constructs were the best predictor for resilience. However, media exposure was insignificant because they were in survival mode when it threatened the risk group's lives. So, this makes them prone to rely more on their knowledge, optimistic thinking, and their own family to help their resilience. Hence this has made them think the role of media is less important in resilience. This study has managed to contribute some useful suggestions for helping risk groups protect themselves during a pandemic. Critically, these findings can update relevant authorities in designing effective interventions to support risk groups by strengthening communication factors associated with resilience.